Efektivitas Metode Make a Match dalam Pembelajaran Pendidikan Agama Islam Di Smk Muhammadiyah 1 Kota Tegal - Bahri, Saeful; Jihan Sonia; Stefani Kusuma Dewi; Ahmad Nur Faizin; Iqbal Fadhilah (CV. Kalimasada Group, 2025)
This study aims to measure the effectiveness of the Make a Match method in teaching Islamic Education (PAI) at SMK Muhammadiyah 1 Kota Tegal. The Make a Match method is chosen because it is believed to be able to increase students' learning motivation and a deeper understanding of PAI concepts. This research uses a quasi-experimental research design with an experimental group taught using the Make a Match method and a control group taught using conventional methods. The results of this study are expected to contribute to the development of more effective and interesting PAI learning models for vocational high school students.